2006
DOI: 10.1038/sj.emboj.7601453
|View full text |Cite
|
Sign up to set email alerts
|

Repression of ADH1 and ADH3 during zinc deficiency by Zap1-induced intergenic RNA transcripts

Abstract: The transcriptional activator Zap1 induces target gene expression in response to zinc deficiency. We demonstrate that during zinc starvation, Zap1 is required for the repression of ADH1 expression. ADH1 encodes the major zinc-dependent alcohol dehydrogenase that is utilized during fermentation. During zinc starvation, Zap1 binds upstream of the activator Rap1 and induces an intergenic RNA transcript, ZRR1. ZRR1 expression leads to the transient displacement of Rap1 from the ADH1 promoter resulting in ADH1 repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 35 publications
3
110
1
Order By: Relevance
“…S. cerevisiae contains multiple alcohol dehydrogenases. While the enzymes encoded by ADH1, -2, -3, and -5 all require Zn as a cofactor, Adh4p uses Mg. ADH4 has been shown to be regulated by Zap1p, while expression of the Znrequiring isoenzymes has been reported to be decreased upon Zn depletion (presumably via Rap1p) (8). In agreement with earlier findings, ADH4 was strongly up-regulated in response to Zn limitation irrespective of the aeration conditions.…”
Section: Resultssupporting
confidence: 87%
“…S. cerevisiae contains multiple alcohol dehydrogenases. While the enzymes encoded by ADH1, -2, -3, and -5 all require Zn as a cofactor, Adh4p uses Mg. ADH4 has been shown to be regulated by Zap1p, while expression of the Znrequiring isoenzymes has been reported to be decreased upon Zn depletion (presumably via Rap1p) (8). In agreement with earlier findings, ADH4 was strongly up-regulated in response to Zn limitation irrespective of the aeration conditions.…”
Section: Resultssupporting
confidence: 87%
“…In other cases, transcriptional interference of tandem promoters may occur through transcription factor dislodgement by advancing RNAP (32)(33)(34). This may also be the case for P2 and P1.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies revealed that transcription of ncRNAs plays certain functional roles. The effects of these transcripts could be repressive (Martens et al 2004;Bird et al 2006;Hongay et al 2006;Camblong et al 2007;Houseley et al 2008) or stimulatory (Uhler et al 2007) for transcription. The gene PHO5 represents the first example of transcriptional activation by a ncRNA: In this case, the transcription of an noncoding antisense RNA initiated at the 39 end of the gene activates full-length PHO5 expression (Uhler et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings in human, mouse, and Saccharomyces cerevisiae demonstrate that these ncRNAs play roles in the regulation of gene expression (Azzalin et al 2007;Houseley et al 2007;Rinn et al 2007;Luke et al 2008;Nagano et al 2008;Pandey et al 2008;Schoeftner and Blasco 2008). ncRNAs exhibit their functions through either the transcribed RNAs (Camblong et al 2007;Martianov et al 2007;Berretta et al 2008;Nishizawa et al 2008;Wang et al 2008) or the action of transcription (Martens et al 2004;Bird et al 2006;Hongay et al 2006;Uhler et al 2007;Houseley et al 2008;Hartzog and Martens 2009). Although ncRNAs are predominantly transcribed in the antisense orientation to repress sense transcripts through RNA-mediated transcriptional gene silencing (Hongay et al 2006;Camblong et al 2007Camblong et al , 2009Berretta et al 2008;Houseley et al 2008), other types of ncRNA-mediated gene regulation have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation